Incidentally detected rare normal anatomical variation of the hemiazygous venous system on computed tomography thorax - Abhang Apte; Sarvesh Patil; Devidas B Dahiphale; Sambhaji Pawal; Asmita Suryawanshi; Prasanna Mishrikotkar (Wolters Kluwer Medknow Publications, 2016)
Various normal anatomical variations of azygous and hemiazygous venous system have been described. We report computed tomography features of incidentally detected anatomical variation of the hemiazygous venous system in a patient with interstitial lung disease. The knowledge of normal anatomical variations of the hemiazygous and accessory hemiazygous venous system is important for both to the reporting radiologist as well as the operating surgeon.